Physicochemical, hygienic and microbiological characteristics of raw milk and water in dairy farms in Teresina, PI (Research, Society and Development, 2020)
The lack of quality in milk can cause significant economic and technological losses for both the industry, as well as for producers and consumers. The present work had as objective to evaluate the physical - chemical and hygienic - sanitary characteristics of the raw milk and the water used in the production of the dairy properties of the Municipality of Teresina, PI. 12 milk samples and 12 water samples were collected and analyzed. For the physical-chemical analysis of milk, the Ekomilk total milk analyzer and Dornic acidimeter were used. For microbiological analyzes of milk and water, Total Bacterial Counting (CFU / mL) was performed and for the detection of total coliforms and E. coli (NMP / 100mL in water, Colilert® (IDEXX) was used. % of the properties analyzed are in disagreement with the standards required for food production establishments of animal origin, not simultaneously corresponding to the qualities required for milk quality and water potability.